Gastric Necrosis due to Acute Massive Gastric Dilatation - Ibrahim Aydin (Case Reports in Medicine, 2013)
Gastric necrosis due to acute massive gastric dilatation is relatively rare. Vascular reasons, herniation, volvulus, acute gastric dilatation, anorexia, and bulimia nervosa play a role in the etiology of the disease. Early diagnosis and treatment are highly important as the associated morbidity and mortality rates are high. In this case report, we present a case of gastric necrosis due to acute gastric dilatation accompanied with the relevant literature.